Zeamatin Inhibits Trypsin and α-Amylase Activities - Schimoler-O'Rourke, Rebecca (American Society for Microbiology, 2001)
Zeamatin is a 22-kDa protein isolated from Zea mays that has antifungal activity against human and plant pathogens. Unlike other pathogenesis-related group 5 proteins, zeamatin inhibits insect α-amylase and mammalian trypsin activities. It is of clinical significance that zeamatin did not inhibit human α-amylase activity and inhibited mammalian trypsin activity only at high molar concentrations.